Business management in the development of teaching capacities that promote sustainable entrepreneurship - Soledispa-Rodríguez, Cecilia (2022)
The objective of this research is to demonstrate to what extent the application of the business management program will increase sustainable entrepreneurship among teachers in Educational Units of Guayaquil-Ecuador 2021. The main problem revolves around the lack of knowledge about the relationship between business management and sustainable entrepreneurship since it has not been studied longitudinally. The study observed how sustained entrepreneurship affects the process and the durability of a student's confidence or identification with the teacher; therefore, the findings based on the surveyed population could guide on the most effective resources and educational strategies to develop and maintain motivation and sustainability in entrepreneurship. The most outstanding results revealed that in the pretest of the experimental group 21.1% is in the medium level and 78.9% in the high level; for the control group 29.8% is in the medium level and 70.2% in the high level; after the application of the program the level of this experimental group increased to 100%.  It is concluded that the effectiveness of the program in the social aspect is an important ingredient in the current business education environment and contributes significantly to the general welfare of society.